The Emerald handbook on cryptoassets : investment opportunities and challenges - Baker, H. Kent; Benedetti, Hugo; Nikbakht, Ehsan; Smith, Sean Stein (Emerald Publishing Limited, 2023)
Bitcoin's introduction as the first cryptoasset in 2009 ushered in a new era, generating much interest, excitement, and growth. A cryptoasset is a digital asset using blockchain technology to regulate the generation of new units and verify and secure transactions. Besides cryptocurrencies, other major cryptoassets are security tokens and utility tokens. Cryptoassets are attractive to investors because of potentially high returns and diversification benefits. However, investors entering this market face substantial challenges like the low quality of information, high price volatility, a lack of academically defensible valuation models, and regulatory uncertainty. This book spans the gamut from theoretical to practical while offering the right balance of detailed and user-friendly coverage. It consists of five parts: (1) the cryptoasset landscape, (2) types of cryptoassets, (3) cryptoassets as investment opportunities, (4) trading, reporting, and technical aspects, and (5) other cryptoasset issues. The book skillfully blends scholars' and practitioners' contributions into a single review of critical topics and issues about cryptoassets. The contributors' varied backgrounds ensure different perspectives and a rich interplay of ideas. The book reflects the latest research and offers a guide to understanding cryptoassets and their role in investment portfolios.